2023
DOI: 10.1021/acs.jafc.2c07084
|View full text |Cite
|
Sign up to set email alerts
|

Sesamolin Attenuates Kidney Injury, Intestinal Barrier Dysfunction, and Gut Microbiota Imbalance in High-Fat and High-Fructose Diet-Fed Mice

Abstract: This study investigated the effects of sesamolin on kidney injury, intestinal barrier dysfunction, and gut microbiota imbalance in high-fat and high-fructose (HF−HF) diet-fed mice and explored the underlying correlations among them. The results indicated that sesamolin suppressed metabolic disorders and increased renal function parameters. Histological evaluation showed that sesamolin mitigated renal epithelial cell degeneration and brush border damage. Meanwhile, sesamolin inhibited the endotoxinmediated indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…30 Therefore, the physiological activity of NEPs may be limited to the regulation of intestinal flora and the amelioration of colonic diseases. 21,38 In this regard, we first tested whether consumption of NEPs versus DFs could differentially regulate the composition of gut microbiota in UC mice. Through 16S rRNA sequencing, this study found that NEPs and DFs could increase the richness of the intestinal microbiome of UC mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Therefore, the physiological activity of NEPs may be limited to the regulation of intestinal flora and the amelioration of colonic diseases. 21,38 In this regard, we first tested whether consumption of NEPs versus DFs could differentially regulate the composition of gut microbiota in UC mice. Through 16S rRNA sequencing, this study found that NEPs and DFs could increase the richness of the intestinal microbiome of UC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Clostridium is the main bacterial genus involved in the production of SCFAs, which can significantly increase SCFA levels in the mouse colon. 21 Meanwhile, it has been proved that elevated SCFA levels can suppress colonic inflammatory responses in DSSinduced colitis mice. 28 Therefore, we examined the correlation between the microbiota-released bound polyphenols or microbiota metabolite SCFAs and the biochemical indices in mice with colitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These abnormal alterations further damaged the glomerular and tubular interstitium, contributing to an increased production of extracellular matrix, and thereby resulting in glomerulosclerosis and interstitial fibrosis. , Dietary fats and sugars, primary sources of body energy, are harmful in excess, particularly diets high in fats and fructose (common in modern high-calorie diets), posing significant risks to human health . Long-term consumption of high-fat and high-fructose diets impairs mitochondrial function in the kidneys, ultimately leading to renal injury. As key regulators of cellular energy, mitochondria maintain cellular homeostasis through a sophisticated monitoring system and play a critical role in protecting renal function, making them a promising target for interventions in kidney diseases . Increasing evidence suggests that mitochondrial dysfunction is an early event in renal injury and significantly accelerates the incidence and progression of CKD. , Mitophagy, a form of autophagy that selectively removes damaged and dysfunctional mitochondria to maintain mitochondrial homeostasis, is recognized as a protective mechanism against chronic kidney dysfunction .…”
Section: Introductionmentioning
confidence: 99%